2014
DOI: 10.1063/1.4869460
|View full text |Cite
|
Sign up to set email alerts
|

The changes on physical characteristics of lightning discharge plasma during individual return stroke process

Abstract: A cloud-to-ground lightning with six return strokes has been recorded with a slit-less spectrograph in Qinghai province. According to the spectra of return strokes without continuous current, the electron density, the channel temperature, and the gas pressure have been calculated. Then, the correlativity of these parameters has been analyzed. The results indicate that the total intensity of spectra is positive correlated to the intensity of spectral line, they both decrease with time rapidly; furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Emissions in the near infrared (NIR) are mostly dominated by neutral nitrogen and oxygen and H α emissions, with also a few emission lines from ionized nitrogen. More recently, Xu et al [] study the correlation between the spectral information, the electron density, the channel temperature, and the gas pressure. They concluded that the total intensity of spectra is positively correlated to the intensity of spectral line and they both rapidly decrease with time.…”
Section: Introductionmentioning
confidence: 99%
“…Emissions in the near infrared (NIR) are mostly dominated by neutral nitrogen and oxygen and H α emissions, with also a few emission lines from ionized nitrogen. More recently, Xu et al [] study the correlation between the spectral information, the electron density, the channel temperature, and the gas pressure. They concluded that the total intensity of spectra is positively correlated to the intensity of spectral line and they both rapidly decrease with time.…”
Section: Introductionmentioning
confidence: 99%
“…1, 7 The lightning channel, heated by strong discharge current, can reach a peak temperature of about 30 000 K, thus forms a plasma channel. 8,9 Analysis on lightning spectrum is an effective way to learn the physical parameters of the plasma channel, which is mainly studied in the 1960s and early 1970s. 10 Most works focused on the investigation of the channel temperature.…”
mentioning
confidence: 99%
“…In other words, the temperature of the return stroke channel is still >20000 K after the current drop to half‐peak values. Because of the continuous action of the current, the attenuation of the temperature is slower than that of the current (Xu et al, ). The return stroke channel can maintain a high temperature for a comparatively longer time.…”
Section: Experiments and Analysismentioning
confidence: 99%